MUSIC AND ITS POWER OF MAKING CAMARADERIE - Krishnan R, Ajay; B, Meenu (International Journal of Psychosocial Rehabilitation, 2020)
In the present world cinema is considered as the most complex and powerful art form which influences our life and lifes of those who around us. His Highness Abdullah is a 1990 Malayalam musical drama written by A K Lohithadas and directed by Sibi Malayil. It is a story of a Qawwali singer Abdullah from Bombay, who comes to a palace in Kerala to murder the head of the Royal family Udayavarma thampuran. The assassination of the king is planned by other family members to grab his wealth.Abdullah disguises as a Hindu Brahmin casteical singer to make his job easy.Ultimately he makes a close relationship with the king with his talent of music.This paper is an attempt to show how music plays an important role in bringing people together under one umbrella, irrespective of caste, creed, religion by eradicating all social inequalities and its healing power.